1987
DOI: 10.3109/15563658708992644
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Cocaine Intoxication in a Fourteen Month Old Child Following Topical Administration

Abstract: We report an unexpected cocaine intoxication following the topical administration of 30 mg cocaine in a fourteen month old boy undergoing bronchoscopy for removal of a foreign body. Possible explanations are discussed. The child recovered completely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The effects of systemically absorbed cocaine are well documented and include tachycardia, convulsions, loss of consciousness and respiratory depression, both in adults and children. [1][2][3][4] Cocaine can also potentiate the effects of exogenously administered adrenaline on the heart resulting in arrhythmias, hypertension and death. 1,5,6 The maximum safe dose of cocaine in clinical practice is 200.mg, yet toxic effects have been reported from doses as low as 20.mg suggesting that toxicity from cocaine does not necessarily follow a linear scale of dose to response.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of systemically absorbed cocaine are well documented and include tachycardia, convulsions, loss of consciousness and respiratory depression, both in adults and children. [1][2][3][4] Cocaine can also potentiate the effects of exogenously administered adrenaline on the heart resulting in arrhythmias, hypertension and death. 1,5,6 The maximum safe dose of cocaine in clinical practice is 200.mg, yet toxic effects have been reported from doses as low as 20.mg suggesting that toxicity from cocaine does not necessarily follow a linear scale of dose to response.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, this is also a global problem. 2,3 Death or severe poisonings of children caused by accidental intake or intentional administration were reported for heroin, 4,5 methadone, [6][7][8][9][10][11][12][13][14][15] cocaine, [16][17][18][19][20] and ecstasy. 21 Between them, the number of death cases with methadone is particularly high and has caught attention since the introduction of this drug as an opioid analgesic in 1947 and for opiate withdrawal therapy in the 1960s.…”
Section: Introductionmentioning
confidence: 99%
“…Schou et al reported an unexpected cocaine intoxication following the topical administration of 30 mg cocaine in a 14-month-old infant who underwent bronchoscopy for a foreign body. 86 Passive freebase cocaine inhalation by infants and toddlers exposed to cocaine freebase or crack smoke has resulted in severe disability and death. Bateman and Heagarty reported severe neurological abnormalities in six young children who were exposed to crack.…”
Section: Respiratory Difficulties In Neonates and Infantsmentioning
confidence: 99%